The Creative Turn - Harris, Anne M. author. aut Link
X, 188 p.
Keywords: The conundrum of understanding, practising and teaching contemporary creativity is that it wants to be all things to all people. Almost all modern lists of creativity, creative thinking and how-to ‘becoming creative’ books begin with one premise: the creative individual/artist is not special, rather each of us is creative in a special way and these skills can – and must - be nurtured. Increasingly, industry and education leaders are claiming that creativity is the core skill to take us into a prosperous future, signalling the democratisation of creativity as industry. Yet centuries of association between aesthetics, mastery and creativity are hard to dismantle. These days, it is increasingly difficult to discuss creativity without reference to business, industry and innovation. Why do we love to think of creativity in this way and no longer as that rare visitation of the muse or the elite gift of the few? This book looks at the possibility that creativity is taking a turn, what that turn might be, and how it relates to industry, education and, ultimately, cultural role of creativity and aesthetics for the 21st century. In proliferating discourses of the commodification of creativity, there is one thing all the experts agree on: creativity is undefinable, possibly unteachable, largely unassessable, and becoming the most valuable commodity in 21st-century markets.